Low, but Physiological, Concentration of GLP-1 Stimulates Insulin Secretion Independent of the cAMP-Dependent Protein Kinase Pathway - Makoto Shigeto; Masashi Katsura; Masafumi Matsuda; Seitaro Ohkuma; Kohei Kaku (Elsevier, 2008)
Glucagon-like peptide-1 (GLP-1) induces pancreatic insulin secretion via the cAMP-dependent protein kinase (PKA) pathway. However, the GLP-1 concentration used in the previous in vitro experiments was far from the in vivo concentrations. Alteration of plasma GLP-1 concentration at pM order lowers blood glucose concentration. In this study, we examined the GLP-1 action mechanism at a physiological concentration on insulin secretion. A high concentration of GLP-1 (10 nM) stimulated intracellular cAMP accumulation and insulin secretion was significantly inhibited by KT5720, a selective inhibitor of PKA. Low GLP-1 concentrations (1 pM) also increased insulin secretion without significant accumulation of intracellular cAMP, and KT5720 did not affect insulin secretion. Insulin secretion stimulated by 1 pM GLP-1 was reduced by inhibitors of calcium action, including verapamil, dantrolene, and BAPTA. Thus, we concluded that relatively low GLP-1 concentrations-comparable to in vivo blood concentrations-promoted insulin secretion independent of the cAMP-PKA pathway. This effect was dependent on intracellular Ca2+ concentration. The results of the present study may further the understanding of the dose-dependent response of GLP-1 signal transducing pathways and the complicated mechanism of insulin secretion. Studies of GLP-1 at physiologic concentrations may lead to new developments in studies of pancreatic β-cell function. Keywords:: glucagon-like peptide-1 (GLP-1), cAMP-dependent protein kinase pathway, insulin secretion, intracellular calcium, endoplasmic reticulum